Sleep in Teens With Type 1 Diabetes: Perspectives From Adolescents and Their Caregivers. Issue 6 (December 2018) - Bergner, Erin M.; Williams, Rodayne; Hamburger, Emily R.; Lyttle, Morgan; Davis, Angelia C.; Malow, Beth; Simmons, Jill H.; Lybarger, Cindy; Capin, Rose; Jaser, Sarah S.
Purpose: The purpose of this study is to identify barriers, facilitators, and consequences of obtaining sufficient sleep in adolescents with type 1 diabetes. Methods: Semistructured interviews were conducted with 25 adolescents (52% female, mean age = 15.6 years) and 25 caregivers. Interviews were transcribed and coded using Atlas.ti. A thematic analytic approach was used to identify and organize significant patterns of meaning (themes) and interpret themes across the data. Results: Several barriers were identified, with the most common being the use of electronics before bed and sleep disturbances related to diabetes management. Caregivers described strategies for helping adolescents achieve sufficient sleep, such as enforcing bedtimes and limiting distractions, but many adolescents could not identify facilitators of sleep. Weekday/weekend discrepancies in sleep timing were commonly disclosed. Conclusions: This study is the first to examine the perceptions of barriers and facilitators to obtaining sufficient sleep in adolescents with T1D and their caregivers. Results have the potential to inform providers' recommendations regarding sleep, including possible interventions to promote sleep in this high-risk population.